2018
DOI: 10.1161/jaha.118.008703
|View full text |Cite
|
Sign up to set email alerts
|

Liver Disease as a Predictor of New‐Onset Atrial Fibrillation

Abstract: BackgroundImpact of liver disease on development of atrial fibrillation (AF) is unclear. The purpose of the study was to evaluate prevalence of AF in the setting of liver disease and whether increasing severity of liver disease, using Model for End‐Stage Liver Disease (MELD), is independently associated with increased risk of AF.Methods and ResultsRetrospective data analysis of 1727 patients with liver disease evaluated for liver transplantation between 2006 and 2015 was performed, and patient characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
0
53
0
Order By: Relevance
“…Unlike the situation in patients without cirrhosis, prolonged QTc is not considered a risk factor for torsade de pointes ventricular tachycardia in cirrhosis. Atrial fibrillation is common in ESLD and increases with increasing Model for End‐Stage Liver Disease score . Atrial fibrillation and other dysrhythmias have been associated with increased cardiovascular events in the perioperative period and worse long‐term outcomes …”
Section: Potential Additional Markers Of Ccmmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the situation in patients without cirrhosis, prolonged QTc is not considered a risk factor for torsade de pointes ventricular tachycardia in cirrhosis. Atrial fibrillation is common in ESLD and increases with increasing Model for End‐Stage Liver Disease score . Atrial fibrillation and other dysrhythmias have been associated with increased cardiovascular events in the perioperative period and worse long‐term outcomes …”
Section: Potential Additional Markers Of Ccmmentioning
confidence: 99%
“…Atrial fibrillation is common in ESLD and increases with increasing Model for End-Stage Liver Disease score. (58) Atrial fibrillation and other dysrhythmias have been associated with increased cardiovascular events in the perioperative period and worse long-term outcomes. (59,60)…”
Section: Biomarkersmentioning
confidence: 99%
“…After excluding duplicates, based on the titles and abstracts of 89 citations (in accordance with the aforementioned exclusion criteria of the meta‐analysis), we initially identified 11 potentially relevant studies from PubMed, Web of Science and Scopus databases prior to December 14, 2018 (date last searched). After examining the full text of these 11 publications, we further excluded 2 studies, because of unsatisfactory inclusion criteria ( n = 1) or unsatisfactory outcome measures ( n = 1), as specified in the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…We used STATA® 14.2 (StataCorp, College Station, Texas) for all statistical analyses. the full text of these 11 publications, [11][12][13][14][15][16][17][18]24,25 we further excluded 2 studies, 24,25 because of unsatisfactory inclusion criteria (n = 1) or unsatisfactory outcome measures (n = 1), as specified in the PRISMA flow diagram.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Prevalence of AF in the general population is approximately 1%-2% in the US 14 . However, regarding the incidence and prevalence of AF in patients with liver cirrhosis, existing publications yielded inconsistent results [15][16][17][18][19][20][21][22] . Some data suggested that cirrhosis might confer a protective effect against the occurrence of AF 15,23 .…”
Section: Introductionmentioning
confidence: 99%